I. SOME PROBLEMS INVOLVED IN A PROPOSED TWELVE-YEAR SCIENCE PROGRAM FOR THE PUBLIC SCHOOLS. - Watkins, Ralph K. (Science Education, 1938)
The article reports on some difficulties associated with a twelve-year program of science instruction for public schools in the U.S. The program involves providing sequences of instruction in English, social studies, mathematics, natural science, foreign languages, and others in addition to curricular or extra-curricular programs in schools. Chances of smooth functioning of all proponents of this program is very remote. Hence, such a program can be established satisfactorily if they fit into the working realities of an existing school system. Further, it is reported that the proponents of such a program will also confront psychological problems such as the relationship of the relative maturity, and consequent readiness, of individuals for learning in terms of certain objectives for science teaching.